Administrative Systems in the Thought of Imam Ali (Peace Be Upon Him) Between Authenticity and Modernity: A Comparative Study - Ahmed Abdulkareem Al-Azzawi, Asst. Lect.; Ali Aghanori, Asst. Prof.Dr.; Thamir Noaman Mostaf , Prof. Dr. (lark, 2025)
Through his wise leadership, Imam Ali (peace be upon him) succeeded in establishing the foundations of administrative leadership and structuring administrative organization based on the principles of Islamic law. He undertook various organizational tasks such as appointing the right person to the right position based on training, testing, and professionalism; managing and dividing time; operating based on a priority system; seizing opportunities for success; structuring the administrative hierarchy; balancing centralization and decentralization; delegating authority; maintaining unified coordination; and developing solutions to crises and overcoming them. His administrative leadership and strong organizational skills enriched society by helping it overcome hardships and achieve security and stability. Until the end of his life, he continued to emphasize the importance of organization, as evidenced by his advice: "I advise you both, all my children, my family, and anyone who receives this letter, to fear God and to organize your affairs." (Abdah, 1412 AH: 7). He assigned duties carefully, showed concern for the community and employees, valued interpersonal relations, and focused on the outcomes and objectives. The solidity of Imam Ali’s administrative system and the strength of his coordination led to the formation of a powerful state that preserved Islamic civilization. Imam Ali (peace be upon him) employed the tools of administrative leadership, wisdom, integrity, honesty, planning, and precise organization, all necessary for success. He appointed capable leaders such as Abu Dharr, Malik al-Ashtar, Ammar ibn Yasir, Al-Miqdad, and Salman al-Muhammadi to support the administrative system and contribute to the enduring success and civilization of Islam.
Keywords: Organization, Caliphate, Governors, Administrative Work